Shift of power in contemporary governance and critical aspects towards tourism development - Ragnheiður Björk Sigurðardóttir 1972- (2018)
Governance is a key term in this paper. It describes a process resting upon three dimensions: decision-making, authority and accountability. Governance has seen major changes in the last century. This shift is presented by new methods by which society is governed – sometimes referred to as minimal states, corporate governance, new public management or contemporary governance. Part of this paper examines the development of contemporary governance in historical terms to provide better understanding of current governance issues, used in the findings of this paper. The research in this paper analyzes four strategic reports on tourism in Iceland, published in the last decade in order to examine how principles of governance manifest in discourse on tourism policy in Iceland and what are the critical aspect put forth by stakeholders. A list of governance frameworks focusing on hierarchies, communities, network and markets is listed and findings matched to governance frameworks to which Icelandic authorities adhere. The result is explored in the light of how transferring mobility of powers between different actors can affect democracy and the development of the tourism sector and utilization of its natural resources. This is put in context to the current era in tourism in Iceland, the fact of almost exponential growth in the sector last decade and that tourism in Iceland still lacks a long-term policy. The study reveals some negative hidden aspects that can occur in the governance process, and a lack of framework in working procedures leading to, for example, democratic deficiency. When the outcome is transferred to the development of tourism, it reveals uncertainty for resource utilization of nature resources in Iceland and future development of the tourism sector. Key Words: Governance, tourism, networks, hierarchies, state, private, natural resources, democracy.